PERAMALAN PRODUKSI BANGGAI CARDINALFISH MENGGUNAKAN METODE AUTOREGRESSIVE INTEGRATED MOVING AVERAGE (ARIMA) - Indah Manfaati Nur; Rara Ayu Puspita (Jurnal Karya Pendidikan Matematika, 2021)
The ARIMA (Autoregressive Integrated Moving Average) method is a very appropriate method to use for the short term because the ARIMA method has very accurate accuracy. And also determine a good relationship between the variables to be forecasted with the value used for forecasting. This study uses the ARIMA method. The purpose of the study was to predict the production of Banggai Cardinalfish (Pterapogon kauderni) which is an ornamental fish commodity that is in great demand. High market demand and production predictions are able to provide the market, becoming important information so that potentials and opportunities can be exploited. The accuracy of the resulting forecast is calculated using the MSE (Mean Squared Error) and MAE (Mean Absolute Error) values. Forecasting results from Banggai Cardinalfish production using the ARIMA method were 830.33 in May 2017 with the resulting MAPE value of 176.93 and MAE of 975.23.